In conversation: photographic curatorship and photographic cultures in museums and research institutions - Elizabeth Edwards; Costanza Caraffa; Ruth Quinn (Science Museum Group Journal)
In this article, Curator of Photography and Photographic Technology, Ruth Quinn talks to Professor Elizabeth Edwards and Dr Costanza Caraffa, two leading thinkers on photography. As a historical and visual anthropologist, and former Curator of Photographs at the Pitt Rivers Museum, Professor Elizabeth Edwards has transformed perceptions of photographs as material objects. Dr Costanza Caraffa is Head of the Photothek at the Kunsthistorisches Institut in Florenz. Caraffa has developed leading approaches to the interaction between photographic, archival and academic practice, advocating for archives as places where research is generated, not only through the act of managing, categorising and re-categorising photographs.